The Urgency of Priority Jurisprudence in the Hajj: Maqasid Syariah Approach to Optimizing Ritual Implementation - Intizam, Ikhsan (Civiliza Publishing, 2024)
The Hajj pilgrimage is a pillar of Islam that must be carried out by Muslims who are physically, financially, and securely able. The Hajj rituals have a deep spiritual dimension, but are also full of practical challenges, including the density of pilgrims, time constraints, and various health conditions of pilgrims. This requires a deep understanding of the concept of priority fiqh, which is an approach in fiqh that focuses on determining the priority scale of practices based on maqasid sharia (objectives of sharia). This research aims to examine the urgency of priority fiqh in the Hajj pilgrimage and provide practical solutions for pilgrims in dealing with complex situations during the Hajj. This research uses a descriptive-analytical method by examining classical and contemporary fiqh literature, so that it is expected to be a guideline for Muslims in managing the Hajj pilgrimage optimally. By understanding priority fiqh, pilgrims can ensure that their implementation of worship remains valid, effective, and in accordance with the main objectives of sharia.